Pengenalan Platform Blended learning dalam Kegiatan Pembelajaran di STIT Raden Wijaya Mojokerto - Ikmal, Happy (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
Distance education as a necessity for sustainable learning and technological innovation has driven the educational approach to the forefront of educational practice. The concept of affinity space, a theoretical construction used to analyze literacy activity from a spatial perspective, has gained popularity among scholars of digital literacy studies: modes of reading, writing, and communication made possible by digital media. Schools as institutions are slow to react to the emergence of this new participatory culture; the biggest opportunities for change are currently found in after-school programs and informal learning communities. Schools must pay more attention to encouraging what we call new media literacy. This paper aims to describe: the introduction of the Blended learning platform in learning activities at STIT Raden Wijaya Mojokerto. From the results of the discussion concluded: 1) To maximize the benefits of digital technology and resources, in order to improve teaching differentiation according to student needs, and to foster classroom interaction. This pedagogical approach is built on the foundation that students' active involvement can be achieved through group dynamics and intense face-to-face interaction. 2) the application of the Blended learning model is a necessity, regulations for e-learning are currently being discussed by the government, through the Minister of Research, Technology and Higher Education Muhammad Nasir said "the regulation of online e-learning or lectures in the near future will be issued government. â€3) To switch from a face-to-face learning model or to meet face to face, then changing to online is very needy and requires considerable effort. But this can begin with the blended learning model which is basically a combination of the advantages of learning that is done face-to-face and virtually.